Multinational electronic health records interoperability strategies - Carter, Sterling K.; Anastasia, Christina; Carter, Barbara Mae (Advances in healthcare information systems and administration (AHISA), 2024)
Amidst the relentless tide of global health crises, a critical problem persists: the lack of a unified electronic health record (EHR) system capable of seamlessly tracking and containing the spread of infectious diseases across borders. The unchecked proliferation of diseases, including the rapid transmission of COVID-19 and the recurring threat of zoonotic infections, underscores the urgent need for a coordinated global response. This absence of interoperability hampers effective patient treatment and surveillance and exacerbates the potential for widespread outbreaks of Biosafety Level 4 (BSL-4) pathogens.Multinational Electronic Health Records Interoperability Strategies is a groundbreaking book, and a beacon of hope in the face of escalating health threats. It catalyzes international collaboration and strategic action by offering a comprehensive exploration into the feasibility and design of a multinational or globally interoperable EHR system. For academic scholars and global leaders, the imperative is clear: embrace this solution-oriented approach and champion the cause of a unified, interoperable EHR system as the cornerstone of our collective defense against the relentless march of infectious diseases.